EPR and XRD Spectra of Copper Complexes of 1,4-Phenylene-Bis-Allylthiourea - Jadon, S.P.S.; PRATIBHA (Asian Journal of Chemistry, 2016)
The paramagentic character and tetragonal geometrical structure of both complexes of 1,4-phenylene-bis-allylthiourea with Cu(I) and Cu(II) have been confirmed by their EPR and X-ray powder diffraction spectra.